Bruk av samiske navn innen markedsføring : En multippel casestudie - Hætta, Nils Runar (2014)
The purpose of this study was to investigate the reason why some companies choose to use Sami names of some of their products. A multiple case study with semi-structured interviews was conducted with two Swedish companies: Hilleberg the Tentmaker and Peak Performance. In the analysis three categories was identified: The Sami language in marketing, the significance of associations on the use of product names in Sami and the importance of Sami product name in marketing. The result of this study shows that words in Sami often is customized when naming products, that it is often associations that inspire the use of Sami name on products and that Sami product names are used with or without a marketing strategy. Validerat; 20140514 (global_studentproject_submitter)